20000 leagues under the sea - Verne, Jules (Boston, Mass: Thomson Heinle, 2005)
A nineteenth-century science fiction tale of an electric submarine, its eccentric captain, and undersea world, which anticipated many of the scientific achievements of the twentieth century
Keywords: Science fiction; Dogs fiction; Underwater exploration -- Fiction